Mucoperiosteal Flap Necrosis after Primary Palatoplasty in Patients with Cleft Palate - Rossell-Perry, Percy; Cotrina-Rabanal, Omar; Barrenechea-Tarazona, Luis; Vargas-Chanduvi, Roberto; Paredes-Aponte, Luis; Romero-Narvaez, Carolina (Archives of Plastic Surgery, 2017)
Background The prevalence of flap necrosis after palatoplasty in patients with cleft palate. The prevalence of mucoperiosteal flap necrosis after palatoplasty remains unknown, and this complication is rare. This event is highly undesirable for both the patient and the surgeon. We present here a new scale to evaluate the degree of hypoplasia of the palate and identify patients with cleft palate at high risk for the development of this complication.Methods In this case series, a 20-year retrospective analysis (1994–2014) identified patients from our records (medical records and screening day registries) with nonsyndromic cleft palate who underwent operations at 3 centers. All of these patients underwent operations using 2-flap palatoplasty and also underwent a physical examination with photographs and documentation of the presence of palatal flap necrosis after primary palatoplasty.Results Palatal flap necrosis was observed in 4 cases out of 1,174 palatoplasties performed at these centers. The observed prevalence of palatal flap necrosis in these groups was 0.34%.Conclusions The prevalence of flap necrosis can be reduced by careful preoperative planning, and prevention is possible. The scale proposed here may help to prevent this complication; however, further studies are necessary to validate its utility.
Keywords: Cleft palate; Craniofacial abnormalities; Congenital diseases